2004
DOI: 10.1108/09596110410559131
|View full text |Cite
|
Sign up to set email alerts
|

Industry internships: feedback from participating faculty and industry executives

Abstract: This study investigates the experiences of both faculty and hosting property executives with internship programs offered through the Council for Hotel, Restaurant, and Institutional Education. Surveys were sent, via myriad methods, to participants asking for a summary of their experiences and suggestions for improvement. Also of interest was the feedback from hosts; therefore, surveys were also sent to all hosting company representatives for similar feedback. It was discovered that internships are of growing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…Tacit knowledge is particularly relevant to hospitality faculty, who are expected to possess some practical industry experience in order to effectively teach their subject matter as well as conduct research. Hospitality instructors with significant industry experience reported that practical knowledge has proven invaluable in both the classroom (Chandler & Faiola, 2009) and research projects (Harris & Zhao, 2004). For example, faculty indicated that related industry experience was an important resource when they were developing and teaching their courses (Chandler & Faiola, 2009).…”
Section: Tacit Knowledge Gained Through Practical Experiencementioning
confidence: 98%
See 1 more Smart Citation
“…Tacit knowledge is particularly relevant to hospitality faculty, who are expected to possess some practical industry experience in order to effectively teach their subject matter as well as conduct research. Hospitality instructors with significant industry experience reported that practical knowledge has proven invaluable in both the classroom (Chandler & Faiola, 2009) and research projects (Harris & Zhao, 2004). For example, faculty indicated that related industry experience was an important resource when they were developing and teaching their courses (Chandler & Faiola, 2009).…”
Section: Tacit Knowledge Gained Through Practical Experiencementioning
confidence: 98%
“…For example, faculty indicated that related industry experience was an important resource when they were developing and teaching their courses (Chandler & Faiola, 2009). Even those faculty participating in hospitality industry internship programs reported increased excitement and appreciation for innovative research opportunities (Harris & Zhao, 2004). In addition, studies have shown high correlations between levels of tacit knowledge and research productivity (Wagner & Sternberg, 1985).…”
Section: Tacit Knowledge Gained Through Practical Experiencementioning
confidence: 99%
“…Notwithstanding these qualifications, in relation to the outsource model, it is understood that there is a high likelihood that an internship (a form of outsourcing), will embrace some F&B experience (Harris and Zhao, 2004). For this reason the internship has been included in analysis, but as a separate category -outsource (internship).…”
Section: Phase Two -National Surveymentioning
confidence: 99%
“…Internships are a common feature in tourism and hospitality programs, and research has tracked the attitudes of students (e.g., Busby, 2005;Cho, 2006;Ju, Emenheiser, Clayton, Sue, & Reynolds, 1998;Lam & Ching, 2007;Walo, 2001;Waryszak, 1997), industry (Harris & Zhao, 2004;Lee, Lu, Jiao, & Yeh, 2006), and multiple stakeholders (Beggs, Ross, & Goodwin, 2008;Collins, 2002;Moscardo & Pearce, 2007;Zopiatis, 2007).…”
Section: Project Conceptualizationmentioning
confidence: 99%